Improving access to post-exposure prophylaxis for Lyme disease: a role for community pharmacists. (13th November 2019) - Baron, G; Pinsonneault, L; Binet, A; Philie, C-A; Bonapace-Potvin, M; Lio, S
Abstract: Issue: Virtually non-existent in Eastern Townships (ET) before 2010, Lyme disease incidence rate reached 52 confirmed cases per 100 000 in some districts in 2018, leading to post-exposure prophylaxis (PEP) recommendation by public health. To improve access to PEP, community pharmacists can now screen and initiate PEP under a collaborative practice agreement (CPA) with the regional Medical Officer of Health. Knowledge, attitudes and practices of pharmacists regarding Lyme disease PEP were surveyed after implementation of this measure. Description of the problem: 312 community pharmacists practicing in ET were invited, in October 2018, to complete an online survey, based on Godin's integrative model (2012), with questions on professional characteristics, knowledge of CPA, attitudes about PEP, and facilitators and barriers to the use of CPA. Pharmacist's practices were evaluated using 8 clinical vignettes. Vignette-specific and a global score were calculated. Bivariate analyses were done to test the association between global score and knowledge, attitudes, facilitators and barriers. Results: Response rate was 13.8%. Most pharmacists knew (97.4%) and were in favor (93.1%) of the CPA, and believed it was effective to prevent Lyme disease (96.4%). The main barriers reported to using the CPA were related to the assessment of PEP criteria. With regards to practice, pharmacists answered correctly for clients presenting all criteria for PEP (80.6%), aged < 8 y.o. (51.6%), who had their tick removed for >72 hrs (67.7%), already presenting with symptoms (32.3%) or who had exposure in a non-endemic area (38.7%). Finally, none of the variables studied were associated with the global score. Lessons: This measure has now been expanded in other endemic regions in Quebec and a provincial CPA is under development. These results will help guide the development of the provincial CPA, specifically to better consider and to provide guidance regarding PEP contraindications. Key messages: Pharmacist-initiated PEP is an innovative approach to increase timely population access to an essential preventive measure in the fight against Lyme disease in endemic districts. Additional guidance is required for pharmacists with regards to assessment of PEP criteria in future CPAs.